Prevention and Control of Dengue Fever among Urban Population (Medical Forum Monthly, 2021)
Objective: To assess the perceptions of urban community about Dengue Fever and its preventive & control measures among the patients visiting OPD.Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the public sector secondary level health care facility Shah Bhittai Hospital Latifabad Hyderabad from January, 2020 to June 2020 for a period of six months.Materials and Methods: A sample size of 308 was obtained and participants were selected by using non-probability purposive sampling technique and all the patients above 18 years of age of both gender, residing at urban area of district hyderabad, having fever visiting at outpatients department of Shah bhittai Hospital Hyderabad were included after getting the informed and written consent. Ethical approval was taken from the ethical committee of LUMHS, Jamshoro. The data was collected on a pre-tested structured questionnaire. We have used SPSS version 16.0 software for both data entering and analysis.Results: A Total 308, participants, who fulfilled the inclusion criteria were included in this study. Out of them majority (82.5%) of participants were female while (17.5%) were males, whereas majority of the participants belongs to the lower class (73.4%) while 24.4% were having middle class economic status. A substantial number of responded (80%) heard and considered dengue fever as a serious illness.Conclusion: There is satisfactory awareness and practices towards preventive measures against dengue fever while inadequate knowledge about cause, mode of transmission of dengue fever.